2017
DOI: 10.1093/jee/tox031
|View full text |Cite
|
Sign up to set email alerts
|

The Synergistic Effects of Almond Protection Fungicides on Honey Bee (Hymenoptera: Apidae) Forager Survival

Abstract: The honey bee (Apis mellifera L.) contributes ∼$17 billion annually to the United States economy, primarily by pollinating major agricultural crops including almond, which is completely dependent on honey bee pollination for nut set. Almond growers face constant challenges to crop productivity owing to pests and pathogens, which are often controlled with a multitude of agrochemicals. For example, fungicides are often applied in combination with other products to control fungal pathogens during almond bloom. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 59 publications
(35 citation statements)
references
References 6 publications
0
34
0
1
Order By: Relevance
“…However, in recent years there have been some conflicting information from studies which have questioned the safety of this product to pollinators (Mussen et al (2004); Ladurner et al 2005Ladurner et al , 2008Fisher et al 2017). The product has been registered for several decades now and has played a critical role in significantly improving yields for farmers, especially in critical crops such as almonds in California and oil seed rape in Canada.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, in recent years there have been some conflicting information from studies which have questioned the safety of this product to pollinators (Mussen et al (2004); Ladurner et al 2005Ladurner et al , 2008Fisher et al 2017). The product has been registered for several decades now and has played a critical role in significantly improving yields for farmers, especially in critical crops such as almonds in California and oil seed rape in Canada.…”
Section: Discussionmentioning
confidence: 99%
“…Especially with insecticides, eliminating the pest while protecting the pollinators can be a difficult task because most pollinators are insects that share a similar physiology. However, fungicide loads in pollen are often higher than any other pesticide category (Pettis et al 2013), and some studies have shown that fungicides can affect the pollinators if sprayed (Fisher et al 2017) or ingested (Mussen et al 2004) at certain doses. Even though a fungicide is targeted at very different organisms, the physiology of fungal pathogens (e.g., Sclerotinia sclerotiorum, which causes sclerotinia stem rot) is considerably different from that of the honeybee.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations